Evaluation of pathologies associated with hyperhomocysteinemia in human autopsy brain tissue. (20th December 2022) - Weekman, Erica M; Winder, Zachary; Rogers, Colin B; Abner, Erin L; Patel, Ela; Dugan, Adam; Fister, Shuling X; Wasek, Brandi; Bottiglieri, Teodoro; Fardo, David W.; Wilcock, Donna M
Abstract: Background: Vascular contributions to cognitive impairment and dementia (VCID) are one of the leading causes of dementia; VCID affects roughly 10‐40% of all dementia patients. A major, yet underrecognized, modifiable risk factor for VCID is hyperhomocysteinemia (HHcy). Defined as elevated levels of plasma homocysteine (a non‐protein‐forming amino acid), most late‐life HHcy is caused by impaired B vitamin absorption. Although HHcy has been recognized as a risk factor for VCID, studies aimed at identifying pathologies associated with HHcy have been lacking. Method: To determine pathologies associated with HHcy, we identified 31 autopsied research volunteers with antemortem homocysteine levels; 13 cases had normal plasma homocysteine levels (>14μmol/L) and 18 had high plasma homocysteine levels (<14μmol/L). We then measured levels of homocysteine and related metabolites in both plasma samples taken closest to autopsy and frontal cortex. Next, we determined whether the level of plasma homocysteine was associated with several markers identified via immunohistochemistry, including Aβ, PHF‐1, IBA‐1 and GFAP. Plasma and brain protein markers for inflammation and angiogenesis were also measured to determine associations with plasma homocysteine. Finally, we used the Human Neuroinflammation NanoString panel to determine gene expression changes of inflammatory markers associated with high homocysteine levels in the frontal cortex and occipital lobe. Result: Plasma metabolite analysis showed patients who had elevated levels of homocysteine also had increased levels of several homocysteine cycle metabolites such as cysteine, S‐adenosyl‐homocysteine, cystathionine and choline. Flt1, an angiogenic marker, and IL5, an inflammatory marker, had a positive correlation with increased plasma homocysteine. No correlation between IBA‐1 or GFAP immunohistochemistry with plasma homocysteine was found. Gene expression showed that most genes were downregulated in the presence of high plasma homocysteine, including many significant genes involved in apoptosis, growth factor and cytokine signaling, and the innate and adaptive immune response. Conclusion: These preliminary data show that increased plasma homocysteine correlates with protein inflammatory and angiogenic markers and with a significant downregulation of inflammation‐related gene expression markers in the brain. Overall, this could reflect impaired normal immune function, providing possible mechanisms by which hyperhomocysteinemia induces cognitive deficits and cerebrovascular damage.